Hubungan Persepsi Body Image dengan Status Gizi Remaja Pada Siswa SMPN 8 di Pekanbaru - Yessi Marlina; Yanti Ernalia (Jurnal Kesehatan Komunitas, 2020)
The impact of body image’s dissatisfaction can be a leading factor for weight loss diet. If it is not balanced with knowledge of a healthy diet, adolescents can get caught in the wrong diet, causing a decrease in nutritional status, iron deficiency, etc. The objective of this study is to determine the relationship between body image perceptions and nutritional status of SMPN 8 students in Pekanbaru. This study is a cross-sectional study with total samples were 160 students which choosen randomly. The perception of body image was obtained from BSQ34 quistionnaire and nutritional status using weight scale and microtoise. Analyzed data using simple regression test. The results showed a positive correlation between body image and nutritional status (p=0,000; r=0,526). Each increase 1 point score of body image, the body mass index predicted will increase by 0.03kg/m2. Total respondents who were satisfied with their body was 62.5% and dissatisfied were 37.5%. The nutritional status of respondents were 3.1% very thin, 6.3% thin, 63.8% normal, 18.1% obese and 8.8% obese. The need for a psychological approach from school to increase student’s confidence of their own body.